2011
DOI: 10.1097/aln.0b013e3181fef34e
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cerebral Oxygen Saturation and Clinical Outcomes in Cardiac Surgery

Abstract: Background:The current study was designed to determine the relation between preoperative cerebral oxygen saturation (ScO 2 ), variables of cardiopulmonary function, mortality, and morbidity in a heterogeneous cohort of cardiac surgery patients. Methods: In this study, 1,178 consecutive patients scheduled for on-pump surgery were prospectively studied. Preoperative ScO 2 , demographics, N-terminal pro-B-type natriuretic peptide, high-sensitive troponin T, clinical outcomes, and 30-day and 1-yr mortality were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
170
5
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(207 citation statements)
references
References 35 publications
20
170
5
12
Order By: Relevance
“…There were no significant differences in any of these parameters between the two groups of patients. Median (IQR [range]) length of stay in ICU and in hospital was 1 (1-1 [1][2][3][4][5][6][7][8][9][10][11][12]) and 9 (6-12 ) days, respectively, in the CPB group, and 1 (1-1 [1][2][3][4][5][6][7][8]) and 8 (6-11 [4][5][6][7][8][9][10][11][12][13][14][15]) days for patients in the no-CPB group (p = 0.840 and p = 0.552, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant differences in any of these parameters between the two groups of patients. Median (IQR [range]) length of stay in ICU and in hospital was 1 (1-1 [1][2][3][4][5][6][7][8][9][10][11][12]) and 9 (6-12 ) days, respectively, in the CPB group, and 1 (1-1 [1][2][3][4][5][6][7][8]) and 8 (6-11 [4][5][6][7][8][9][10][11][12][13][14][15]) days for patients in the no-CPB group (p = 0.840 and p = 0.552, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…It gives an indication of the balance between oxygen delivery and oxygen consumption, which may have prognostic value. A recent study showed that pre-operative cerebral oximetry values predicted various postoperative outcomes after coronary surgery using CPB [12]. Other studies have shown a correlation between the severity and duration of cerebral desaturation, with or without CPB, and subsequent postoperative cognitive dysfunction [13,14], although the evidence is somewhat weak [15].…”
Section: Introductionmentioning
confidence: 97%
“…Its low value has been observed to correlate with a high risk of surgery according to the EuroSCORE as well as poor diastolic and systolic functions of the left ventricle and to indicate an increased risk of postoperative delirium [17,18]. Heringlake and co-workers [19] have demonstrated the lowest value of brain saturation immediately prior to cardiac surgery, i.e. below 50%, is associated with increased 30-day and annual mortality.…”
Section: Use Of Brain Oximetry During Cardiac Surgerymentioning
confidence: 99%
“…Maintenance of rSO2 within 10% to 20% of baseline in these patient groups reduced complications (4,5). Although the normal rSO2 in a fit young patient may be around 60% to 70%, representing a venous weighted measure of cerebral tissue oxygenation, values as low as 35% are sometimes seen in elderly patients presented for surgery and may be a significant predictor of poor outcome (6). A recent study suggests that rSO2 is a potentially important biomarker that should be measured in heart failure patients and suggests that it may be a useful marker of target organ perfusion (7).…”
Section: Introductionmentioning
confidence: 99%